Systematic Literature Review (SLR): Explorations flood systems theory and appropriate modeling - Arham, Brenda; Muhamad Dimyati (Journal of Smart Agriculture and Environmental Technology, 2024)
Urban flood risk assessment conducts a comprehensive evaluation of hazard formative factors, hazard formative environment, hazard-affected bodies, and capabilities for disaster prevention and reduction in order to obtain an accurate assessment of flood risk levels. The current study aimed to conduct a systematic review of the existing literature on engagement outcomes, focusing on high-quality studies Each step of the SLR method and their results are explained in detail in the following subsections using SLR performed. Using the SLR method can help answer the objectives of this research in the form of: What type of modeling to overcome flooding This research uses the SLR method which aims to recognize, review, and evaluate Using bibliometric analysis.To achieve the goal of SLR, the variables of interest are organized based on the general characteristics of the article and the specific parameters used general  information about the article includes year of publication, type of analysis (quantitative, qualitative, cartographic or mixed), type and scale of  research, and the country or region where the research was conducted. The model consists of three components, including rainfall runoff, river channels, and flooding The flow in the channel was generated with a 1D diffusion wave model, and the outflow on the slope was generated with a 2D model.This article showed the basic steps that need to be followed to conduct SLR This method generates topic-specific existing knowledge, trends, and observed gaps and helps to draw relevant conclusions for policy makers and the scientific community. and the appropriate modeling is Press RRI refers to 2D grid-based fluid dynamics and is a model that combines a hydrological model and a flood model.